Reproductive decision-making in women living with human immunodeficiency virus: A systematic review. (January 2018) - Leyva-Moral, Juan M.; Palmieri, Patrick A.; Feijoo-Cid, María; Cesario, Sandra K.; Membrillo-Pillpe, Nataly Julissa; Piscoya-Angeles, Patricia N.; Goff, Marilyn; Toledo-Chavarri, Ana; Edwards, Joan E.
Abstract: Objectives: Analyze and synthesize the research evidence to understand the reproductive decisions made by women living with HIV from the beginning of the epidemic to the present. Evaluate the barriers and the facilitators for reproductive decision-making. Identify areas of strength, improvement, and those requiring further research. Design and data sources: Systematic review following the PRISMA guideline. PubMed, CINAHL, PsycINFO, Cochrane Library, SocINDEX, Embase, and Scopus databases were searched from 1985 to 2016 using the following Keywords: HIV, AIDS, pregnancy, reproduction, and decision-making. Study selection: A total of 42 research papers were included in this review. Initially, 1563 papers were identified for the review by database (n = 1544) and hand (n = 19) searches. With three review levels, 1521 papers were excluded (title review, n = 1272; abstract review, n = 136; and full paper review, n = 113). Studies published in English in peer-reviewed journals using both quantitative and qualitative methods and addressing reproductive decisions in women living with HIV were included. Thirdly, inclusion eligibility was assessed by title, abstract, and full text. Review methods: Random allocation conducted by the primary researcher assigned an equal number of papers to each researcher for review, including detailed instructions with an abstraction form. Discrepancies were resolved by two researchers. Research quality was assessed using the NCHBL Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies, the Critical Appraisal Skills Programme for the qualitative studies and its version for systematic reviews Results: The review included 42 papers, both quantitative (n = 24) and qualitative methods (n = 14). Most studies were completed by physicians (n = 16) or nurses (n = 15). More than two-thirds of the studies were performed in urban settings with predominantly African-American women (n = 27). Eight factors were identified as influencing the reproductive decision-making process in women living with HIV: 'Socio-demographic, Health status and Pregnancy', 'Religion and spirituality', 'Beliefs and Attitudes about Antiretroviral Therapy', 'Healthcare providers', 'Significant others', 'Motherhood and fulfillment', 'Fear of perinatal infection and infection of partner(s)', 'Birth control and pregnancy management'. Conclusions: Health care providers are not providing patient-centered care by applying scientific evidence to their practice when advising women with HIV in making reproductive decisions. Despite the strong evidence indicating pregnancy for women with HIV results in a safe birthing trajectory, one not likely to jeopardize the health of the either the mother or fetus, providers continue to recommend the women with HIV avoid pregnancy and neglect to invite partners to participate in the discussion.